Optimalisasi Potensi Desa dalam Rangka Merintis Desa Wisata Paranggupito Kabupaten Wonogiri - elisa dwi rohani rohani (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
Optimization of village potential in the order of pioneering Paranggupito tourism village, Wonogiri Regency. Along with the development of tourist villages, the Central Java Provincial Government responded to this condition with the existence of the Central Java Provincial Regulation No. 2 of 2019 concerning the empowerment of tourist villages in Central Java Province One of the districts in Central Java located at the southern tip of which is currently working to build a tourist village in Wonogiri Regency. Currently, Wonogiri Regency has 6 tourist villages that have already obtained SK as tourism villages from the Wonogiri Regency Youth and Sports and Tourism Office in 2020, one of which is the Paranggupito tourism village. This research will focus on pioneering tourism villages by maximizing the existing potential. The purpose of this research is to multiply the potential and tourist attractions, mapping the potential of tourism villages, and develop the concept of a tourism village with the activities offered by the strategy of packaging tourism villages into tour package products. In this study, descriptive qualitative research methods are used by describing and mapping the potential of tourism villages, as well as compiling village tour packages. In addition, non-physical development will also be carried out including the development of human resources, both technical and managerial skills for tourism village managers, building cooperation networks, and compiling marketing media to be used. In pioneering Paranggupito tourism village, it is made in 2 concepts that are oriented towards the tourist market to be targeted, concept 1 which emphasizes more on educational and adventure tourism with the target market being young people who like an adventure.